Impact of Thalassemia Centre on awareness of parents of Thalassemic patients about the disease: Comparative study in Muzaffarabad and Kotli districts of Azad Kashmir - Ahmed, Mahmood; Sharif, Muhammad Shabbir; Yaqoob, Rashid; Nadeem, Malik Sajjad Ahmed; Haroon, Zeeshan; Iqbal, Toqueer (Pakistan Journal of Physiology, 2019)
Background:- Thalassemia major is a genetic blood disorder usually presenting in first year of life. Its management requires huge financial, technical, social and psychological support. However preventive measures and proper management reduce morbidity and mortality. It is of utmost importance to get an insight about knowledge of parents who play a vital role in care. In knowledge deficient groups, interventional strategies can help improve patient care. The objective of the study was to assess the awareness of parents of thalassemia patients about cause (inheritance), prevention and treatment. Methods: This is quasi experimental study. Data collected by simple convenient sampling. A questionnaire was designed after consulting studies of Armeli et al and Maheen et al. Questionnaire containing 32 items was used on 85 parents of children attending blood bank AK CMH Muzaffarabad and thalassemia centre DHQ Hospital Kotli. Data was analyzed on SPSS. Consenting parents of diagnosed cases of Thalassemia were included in study. Results: Study showed that overall acceptable knowledge about thalassemia was better in respondents from Kotli 32(76.2%) as compared to Muzaffarabad 18(41.9%)(P=0.01). When estimating correct responses in gender and parents with different educational background, significant difference(P=0.04) was found between percentage of correct answers in educated 58.14±5.01 compared to uneducated 51.08±10.9 respondents. Conclusion: Established thalassemia center has a positive impact on awareness about Thalassemia inheritance, prevention and management. Thalassemia centers should be established in all district hospitals where dedicated staff must take care of thalassemia patients. Thalassemia awareness programs, premarital screening and legislation are the need of the day.